Comparative analysis of the incidence of head and neck cancer in south-eastern Poland and in Poland in the years 1990–2012 - Gawełko, Jan; Cierpiał-Wolan, Marek; Kawecki, Andrzej; Wilk, Konrad; Pięciak-Kotlarz, Danuta B.; Sikorski, Damian (Contemporary Oncology/Współczesna Onkologia, 2017)
Aim of the study : To present the changes in the incidence of cancers of the head and neck organs in south-eastern Poland and in the whole country in the years 1990-2012. Material and methods : A retrospective analysis the incidence of cancers of the head and neck organs in south-eastern Poland in the years 1990–2012. Statistical methods used for cancers of ICD-10 C00-C14 and C30-C32. Results: For Poland, the absolute number of cases was 123,120 in the years 1990-2012. For males, the number of cases per year increased from 4468 in 1990 to 4953 in 2012, and for females from 816 to 1442. The percentage share of tumours of the head and neck in all malignant tumours decreased from 10.0% to 6.5% for males and from 2.1% to 1.9% for females. In the years 1990–2012 in south-eastern Poland, for males, the absolute number of cases per year decreased from 335 in 1990 to 286 in 2012. For females, a minimal increase in cases was from 63 to 64 cases. The percentage share of tumours of the head and neck in all malignant tumours decreased from 12.2% to 6.7% for males and from 2.7% to 1.8% for females. Conclusions : Incidences of cancers of the head and neck organs in Poland have seen a slight upward trend in the absolute number of cases over the last two decades. In Poland a decrease in the incidence of cancer of the larynx was reported, with an increase in the incidence of oropharyngeal cancer.